2014
DOI: 10.1039/c3gc41577e
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient separation of rare earths from nickel and cobalt by solvent extraction with the ionic liquid trihexyl(tetradecyl)phosphonium nitrate: a process relevant to the recycling of rare earths from permanent magnets and nickel metal hydride batteries

Abstract: The undiluted ionic liquid trihexyl(tetradecyl)phosphonium nitrate was used for cobalt–samarium and nickel–lanthanum separations by solvent extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
139
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 200 publications
(143 citation statements)
references
References 57 publications
1
139
0
3
Order By: Relevance
“…s at 313 K), which is still significantly lower than observed for other similar bulky metal-loaded IL extraction systems. 21 Moreover, TOC analysis showed that the solubility of [P 8888 ][oleate]…”
Section: Il Synthesis and Characterizationmentioning
confidence: 99%
“…s at 313 K), which is still significantly lower than observed for other similar bulky metal-loaded IL extraction systems. 21 Moreover, TOC analysis showed that the solubility of [P 8888 ][oleate]…”
Section: Il Synthesis and Characterizationmentioning
confidence: 99%
“…The decrease in lanthanide uptake with increasing acidity is likely due to the competitive co-extraction of HNO 3 . 40 The desorption process was almost quantitative when using a 0.1 M HNO 3 solution (Fig. S6), in which H + inhibited the residual ion exchange sites (silanol and titanol) and low nitrate concentration favoured the breakdown of lanthanide nitrate complexes.…”
Section: Batch Uptake Of Lanthanidesmentioning
confidence: 99%
“…This was a new iono-metallurgical approach for the processing of metals in ionic liquids. 201 Other applications include the development of a fluorine-free solvent for the extraction of europium(III) and other trivalent rare earth ions using trihexyl(tetradecyl)phosphonium N,N,N 0 ,N 0 -tetra(2-ethylhexyl)malonate, [P 66614 203 Also of note is the use of mutually immiscible ILs such as 1-ethyl-3-methylimidazolium chloride and [P 66614 ] bis(2,4,4-trimethylpentyl) phosphinate to extract rare earths, 204 the development of a process using [P 66614 ][NO 3 ] to extract rare earths and separate them from nickel or cobalt, 205 and the use of [P 66614 ]Cl for selective extraction and recycling of metals from nickel metal hydride batteries 206 and rare-earths from NdFeB magnets. 207 Extraction of rare earth ions was also studied by Matsumiya et al 208 using tri-n-butylphosphate in combination with [P 2225 ][TFSA].…”
Section: Extraction and Separation Technologies Based On Pilsmentioning
confidence: 99%